Traumatic Wound Dehiscence after Keratoplasty: Characteristics, Risk Factors, and Visual Outcome. (9th July 2015) - Goweida, Mohamed Bahgat; Helaly, Hany Ahmed; Ghaith, Alaa Atef
Abstract : Purpose. The study aimed at evaluating the patients' characteristics, risk factors, complications, and visual outcome of traumatic wound dehiscence after keratoplasty. Patients and Methods . A retrospective case series that included 20 eyes of 20 patients who had undergone a previous keratoplasty procedure followed by traumatic wound dehiscence. Records of the selected patients were reviewed. The mean duration of follow-up after repair was 21 months. Included patients were recalled for the final follow-up visit. Results. The procedure of corneal transplantation was penetrating (PKP) in 16 eyes and deep anterior lamellar keratoplasty (DALK) in 4 eyes. The associated anterior segment injuries included iris prolapse in 17 eyes and lens extrusion in 12 eyes. The associated posterior segment injuries included vitreous hemorrhage in 11 eyes and retinal detachment in 4 eyes. The final BSCVA was 0.1 or better in 5 cases (25 %) and was better than hand motions (HM) to less than 0.1 in 7 cases (35 %). Conclusion. Traumatic wound dehiscence following keratoplasty results in poor visual outcome. Cases following DALK may have less wound extent and better final visual outcome. The dehiscence seems most likely to occur during the first year.